Immunotherapy with CAR-Modified T Cells: Toxicities and Overcoming Strategies - Zhang, Yi; Yang, Ge; Hao, He; Sun, Shangjun; Fu, Yang (Journal of Immunology Research, 2018)
T cells modified via chimeric antigen receptors (CARs) have emerged as a promising treatment modality. Unparalleled clinical efficacy recently demonstrated in refractory B-cell malignancy has brought this new form of adoptive immunotherapy to the center stage. Nonetheless, its current success has also highlighted its potential treatment-related toxicities. The adverse events observed in the clinical trials are described in this review, after which, some innovative strategies developed to overcome these unwanted toxicities are outlined, including suicide genes, targeted activation, and other novel strategies.